White House white-out - Roy, Ron, 1940-; Gurney, John Steven, 1962- (New York : Random House, 2008)
When Dink, Josh, and Ruth Rose visit Washington, D.C., just before Christmas, they are inadvertently caught up in a kidnapping plot that was intended for the president's dog, but also involves the president's stepdaughter and her friend Marshall.
"A Stepping Stone book."
Keywords: Kidnapping -- Juvenile fiction; Dogs -- Juvenile fiction; Washington (D.C.) -- Juvenile fiction; Virginia -- Juvenile fiction; Mystery fiction